The contributions of Indian Muslims to the Ottoman caliphate and the Turkish nation (1874 to 1924) - Khalid, Noor Mohammed (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
Much has indeed been written about the contributions of Muslims of the Indian subcontinent to the tottering Ottoman Empire, and, subsequently, to the Turkish Republic which, de facto, took over the governance from the Caliph-Sultan in the first decade of the twentieth century. However, the existing literature and research published on this subject has, largely, overlooked the role of many stalwarts who did not belong to Northwest India. Moreover, the period which the literature and research published begins mostly from the beginning of the twentieth century, ignoring fully, or in great part, the role of Indian Muslim contributions from the 1870s. Moreover, many moving testimonies available in Urdu have remained untranslated this far. Even where important events have been mentioned, interesting and critical details of the events are missing. Making use of material in Urdu and personal interviews, the exemplary contributions of the scholars of the Deoband, led by Qasim Al-Nanawtwi (1832-1880), in the 1870s figures prominently in the thesis. Also, are brought to the fore the financial contributions from India as compared to the rest of the Muslim world, drawing on the research of a Japanese researcher which does not find mention in the mainstream literature on the subject. Similarly, this thesis focuses on aspects of the Khilafat-inspired Mappila Uprising which have been inadequately dealt with in English works. This researcher undertook a field trip for this purpose and interviewed many contemporary historians in Malabar. Elegiac poems written by Allama Shibli (1857-1914) have been translated into English by the researcher himself and published in this thesis in the context in which they were written. Another first is the English translation of some aspects of the life of Mohammed Ali Jauhar (1878-1931) from his Urdu biography by Daryabadi (1892-1977). To set the context for the narrative, the decline of Muslim political power in India and the decline of the Ottoman empire during the late eighteenth and early nineteenth centuries have been dealt with at length. Additionally, the efforts made in India and Turkey to stem the decline and restore the dignity of the said communities are included. There are many useful lessons that contemporary Muslim minorities can learn from the momentous events that took place during the 1874 to 1924 period mentioned in the thesis.